Corrigendum to “Adulteration in paneer (Indian cottage cheese): A review of practices, detection, and public health implications – a critical analysis”[Food Control 187 (2026) 112163] - A. Surendra Babu; P. Sankarganesh; V. Parthasarathy; K. Rajkumar; Meenatai Gunderao Kamble (Food Control, 2026)

Adulteration in paneer (Indian cottage cheese): A review of practices, detection, and public health implications – a critical analysis - A. Surendra Babu; P. Sankarganesh; V. Parthasarathy; K. Rajkumar; Meenatai Gunderao Kamble (Food Control, 2026)

Three decades of livestock-relevant heat stress intensification along the Indian West Coast: a gridded THI trend and temperature-humidity contribution analysis - Subhradip Bhattacharjee; R. Solomon Rajkumar; V. Paramesha; Parveen Kumar; Basavareddy; Amitava Panja; Subham Singha; Dipak Dey; Prasanna Pal; Rakesh Kumar; Dinesh Kumar (Theoretical and Applied Climatology, 2026)

Integrated spatio-temporal analysis of historical and future projections precipitation variability alongside agricultural production trends in the North Western Himalayan Region - Neha; Sanjeev Dwivedi; V. Kumar; Rajkumar Guria; Manoranjan Mishra; S. K. Srivastava (Theoretical and Applied Climatology, 2026)

Deciphering biocontrol efficacy and in silico mechanistic elucidation of Trichoderma asperellum and Bacillus licheniformis against groundnut stem rot caused by Sclerotium rolfsii - Sivaji Jeevanantham; Renganathan Periyasamy; Suthin Raj Thankaraj; Meena V. Ruppavalli; Annadurai Praveen; Rajendiran Livitha; Rajkumar Sudharsan; Muthusamy Karthikeyan (Physiological and Molecular Plant Pathology, 2026)

Utilization of Genetically Engineered RuBisCO Enzyme for Capturing Carbon Dioxide to Address Environmental Challenges-An Overview - Priya Gupta; Rajkumar Prabhakaran; Nalini Soni; Sangeeta Devendra Kumar Singh; Chinnaperumal Kamaraj; Silambarasan Tamil Selvan; Neethu Asokan; Sudheer D. V. N. Pamidimarri; Balasubramanian Velramar (Water, Air, & Soil Pollution, 2026)

Enhanced dual removal of chromium and lead ions from water using biopolymer modified ferric–alumina layered double hydroxides - V. Nithya Priya; D. Karthigaimuthu; S.Sasi Florence; M. Rajkumar; S.P.Linto Sibi; M.S. Sobana; J. Mobika; V. Vijayalakshmi; P. Ahila (Journal of Environmental Chemical Engineering, 2025)

Flurbiprofen restores rifampicin and isoniazid sensitivity in multidrug-resistant Mycobacterium tuberculosis putatively by inhibiting efflux pumps Rv0194 and Rv0933 - Padmasini Elango; Christy Rosaline Nirmal; Sam Ebenezer Rajadas; Rajkumar Ravi; Naresh Babu Chilamakuru; Azger Dusthackeer V. N. (Folia Microbiologica, 2025)

First record of fruit rot in soursop caused by Lasiodiplodia theobromae in India - Prathibha V. H.; Panjavarnam G.; Daliyamol; Rajkumar; Keerthana S.; Thejasri K. P.; Gangaraj K. P.; Rajesh M. K.; Vinayaka Hegde (Journal of Plant Pathology, 2025)

Production of biologically active recombinant salmon calcitonin in Escherichia coli and fish cell line - A. Nafeez Ahmed; S. Abdul Majeed; G. Taju; S. Suryakodi; S. Mithra; M. J. Abdul Wazith; K. Kanimozhi; V. Rajkumar; A. Badhusha; A. S. Sahul Hameed (Archives of Microbiology, 2025)

Drip irrigation for sustaining high sugarcane ( Saccharum officinarum ) yield in marginally to moderately waterlogged saline vertisols of Karnataka, India - Rajkumar R.H.; Vishwanath J.; Annanagouda V. Karegoudar; Malharimartand J. Kaledhonkar; Anand S.R.; Anilkumar T. Dandekar; Raj Kumar Thakur (Irrigation and Drainage, 2025)
In the Tungabhadra project command, subsurface drainage is used to reclaim waterlogged saline areas, but its adoption is lower due to its high cost and highly skilled in nature. Irrigation water management could sustain high cane yields in mildly affected areas. A field experiment was conducted on waterlogged saline vertisols with sugarcane crops using surface drip, subsurface drip and furrow irrigation with water application amounts of 0.8, 1.0 and 1.2 of evapotranspiration (ET). The subsurface drip at 1.2 ET resulted in more leaching of salts and a higher moisture content. Also it had the highest cane yield (131.0 t ha −1 ), water productivity (WP) (8.30 kg m −3 ) and sugar WP (1.72 kg m −3 ) among the different methods. Among the irrigation levels, the 1.2 ET level had the highest cane yield (124.7 t ha −1 ), lowest WP (6.89 kg m −3 ) and highest sugar WP (1.43 kg m −3 ). The highest benefit–cost ratio was recorded for the subsurface drip treatment. Depth to water table was greater for the subsurface drip treatment compared to the furrow treatment. Therefore, subsurface drip irrigation at 1.2 ET for sugarcane can act as a viable preventive measure for sustaining high cane yield in mildly waterlogged saline vertisols in the command.

Sustainable selenium ions adsorption of cyclodextrin and cellulose functionalized layered double hydroxide/reduced graphene oxide nanocomposites - V. Nithya Priya; M. Rajkumar; V. Rajendran; J. Mobika; S.P. Linto Sibi; B. Veena; V. Vijayalakshmi; P. Ahila (Journal of Water Process Engineering, 2025)

Development of three-dimensional (3D) spheroid culture system from rainbow trout kidney cell line (RTK) for in vitro production of fish viral pathogen - S. Suryakodi; S. Mithra; A. Nafeez Ahmed; K. Kanimozhi; V. Rajkumar; G. Taju; S. Abdul Majeed; A. S. Sahul Hameed (Aquaculture International, 2024)

Zinc solubilization and organic acid production by the entomopathogenic fungus, Metarhizium pingshaense sheds light on its key ecological role in the environment - C.M. Senthil Kumar; Sharon D'Silva; R. Praveena; Anees Kaprakkaden; L.R. Athira Krishnan; M. Balaji Rajkumar; V. Srinivasan; R. Dinesh (Science of The Total Environment, 2024)

Development and characterization of brain cell line from Trachinotus blochii and its application in virological and gene expression studies - A. Nafeez Ahmed; S. Mithra; S. Suryakodi; G. Taju; M. J. Abdul Wazith; K. Kanimozhi; V. Rajkumar; A. Badhusha; S. Abdul Majeed; A. S. Sahul Hameed (Journal of Fish Diseases, 2024)
A permanent cell line, SPB (Snubnose pompano brain) was established from Trachinotus blochii by the explant culture method. It has been sub‐cultured more than 75 passages and showed optimal growth at 28°C using L‐15 medium supplemented with 15% to 20% FBS. The SPB cells were cryopreserved at different passage levels for various applications. SPB cells were composed of fibroblastic and epithelial‐like cells. The SPB cells were tested for mycoplasma contamination which was found to be negative. The origin of the SPB cell line from T. blochii was confirmed by amplification of the mitochondrial cytochrome oxidase I (COI) gene. The transfection efficiency of SPB cell line is 15% assessed by expression of green fluorescent protein using pEGFP‐N1 plasmid. In addition, two CMV promotor plasmids pFNCPE42‐DNA and pcDNAVP28 were transfected to SPB cells and it shows high expression levels of FNCP of fish nodavirus and VP28 protein of white spot syndrome virus by immunostaining. The SPB cells showed susceptibility to SJNNV and the infection was confirmed by RT‐PCR, Western blot, ELISA, TCID 50 and RT‐qPCR. Experimental infection was carried out in T. blochii using SJNNV propagated in SPB cell line and found 100% mortality with clinical signs. The infection was confirmed by RT‐PCR. The SPB cell line can be used for propagation of fish viral pathogens and production of the recombinant proteins.

A comparative study on targeted gene expression in zebrafish and its gill cell line exposed to chlorpyrifos - Abdul Wazith M. J.; Taju G.; Abdul Majeed S.; Mithra S.; Nafeez Ahmed A.; Badhusha A.; Rajkumar V.; Sahul Hameed A. S. (In Vitro Cellular & Developmental Biology - Animal, 2024)

Effect of Pulsed Light Treatment for the Preservation of Coconut Inflorescence Sap - V. Vishnu Priya; M. Balakrishnan; R. Pandiselvam; S. Karthikeyan; P. Rajkumar; M. R. Manikantan; K. Gurusamy; P. Preetha (Sugar Tech, 2024)

Agrosilvopastoral systems for improved crop and fodder productivity and soil health in the rainfed environments of South India - G. Venkatesh; K.A. Gopinath; D.B.V. Ramana; V. Visha Kumari; I. Srinivas; Arun K. Shanker; K.V. Rao; J.V.N.S. Prasad; K. Sammi Reddy; K.B. Sridhar; B. Sarkar; B.M.K. Raju; et al. (Agricultural Systems, 2024)

Humidity activated ultra-selective room temperature gas sensor based on W doped MoS2/RGO composites for trace level ammonia detection - S.P. Linto Sibi; M. Rajkumar; Mathankumar Manoharan; J. Mobika; V. Nithya Priya; R.T. Rajendra Kumar (Analytica Chimica Acta, 2024)

Advances in drying techniques for retention of antioxidants in agro produces - V. A. Athira; E. Gokulvel; A. M. Nandhu Lal; V. V. Venugopalan; Rajkumar; T. Venkatesh (Critical Reviews in Food Science and Nutrition, 2023)

Evaluation of Effect of Tapping Frequency and Lime Coating on the Biochemical Changes and Fermentation Rate of Coconut Inflorescence Sap - V. Vishnu Priya; M. Balakrishnan; S. Karthikeyan; P. Rajkumar; M. R. Manikantan; K. Gurusamy; R. Pandiselvam (Sugar Tech, 2023)

Electronic sensitization enhanced p-type ammonia gas sensing of zinc doped MoS2/RGO composites - S.P. Linto Sibi; M. Rajkumar; Kamaraj Govindharaj; J. Mobika; V. Nithya Priya; R.T. Rajendra Kumar (Analytica Chimica Acta, 2023)

A comparative study on geoeffective and non-geoeffective corotating interaction regions - Jibin V. Sunny; Archana Giri Nair; Megha Babu; Rajkumar Hajra (Advances in Space Research, 2023)

Economic feasibility of subsurface drainage (SSD) to control waterlogging and soil salinity under different scenarios in the Tungabhadra project command, Karnataka, India - Karegoudar A V; Vishwanath J; Rajkumar R H; Anand S R; Polisgowdar B S; Ayyanagowdar M S; Nemichandrapp M; Kaledhonkar M J (Irrigation and Drainage, 2022)
The Tungabhadra irrigation command area (TBP) in Karnataka, India, has three scenarios: the head, mid and tail reach command areas. The head reach has ample good quality canal water availability, and the mid reach area has limited canal water availability. In recent decades, rice–rice monocropping in vertisols, especially by these head and mid reach farmers, has led to not only water shortages but also the development of waterlogging and secondary soil salinization in the tail (lower) reach of the command due to seepage. As the soil salinity in the head reach was less severe, a slightly wider drain spacing of 60 m was adopted over 15 ha. In the case of the mid reach, salinity was slightly higher than the head reach but slightly less than the tail reach, hence 50 m drain spacing was laid out over 24 ha. Due to the slightly higher soil salinity at the tail end of the command, a closer drain spacing of 40 m was adopted over 11 ha. In all these scenarios, the drain depth was 1.0 m. Despite differences in irrigation water availability and different soil salinity conditions, the study clearly indicated over six seasons that the SSD system is a viable solution for the reclamation of waterlogged saline soils and enhancing rice productivity in all three scenarios of the TBP command.

First record of Fusarium falciforme (FSSC 3 + 4) a relevant human pathogen causing root decay of arecanut, Areca catechu L - R. Thava Prakasa Pandian; Shivaji Hausrao Thube; Babu Merin; V. H. Pratibha; M. Rajkumar; Priyank Hanuman Mhatre; Vinayaka Hegde (Journal of Plant Diseases and Protection, 2022)

Temporal trends in frost occurrence and their prediction models using multivariate statistical techniques for two diverse locations of Northern India - Santanu Kumar Bal; Rajkumar Dhakar; P. Vijaya Kumar; Adita Mishra; V. P. Pramod; M. A. Sarath Chandran; V. M. Sandeep; A. V. M. Subba Rao; K. K. Gill; Rajendra Prasad (Theoretical and Applied Climatology, 2021)

Estimation and Validation of Actual Evapotranspiration (ETa) of Maize Wheat Cropping System Using SSEBop Model Over IARI Research Farm, New Delhi, India - Joydeep Mukherjee; Anuradha Sharma; Rajkumar Dhakar; V. K. Sehgal; D. Chakraborty; D. K. Das (Journal of the Indian Society of Remote Sensing, 2021)

Backyard poultry farming for sustained production and enhanced nutritional and livelihood security with special reference to India: a review - U. Rajkumar; S. V. Rama Rao; M. V. L. N. Raju; R. N. Chatterjee (Tropical Animal Health and Production, 2021)

A new strain of white spot syndrome virus affecting Litopenaeus vannamei in Indian shrimp farms - S Sivakumar; S Vimal; S Abdul Majeed; S Santhosh Kumar; G Taju; N Madan; T Rajkumar; S Thamizhvanan; K V Shamsudheen; V Scaria; S Sivasubbu; A S Sahul Hameed (Journal of Fish Diseases, 2018)
White spot syndrome virus ( WSSV )‐infected shrimp samples collected from grow‐out ponds located at Nellore, Andhra Pradesh, India, showed WSSV negative and positive by PCR using primer sets specific to ORF 119 and VP 28 gene of WSSV , respectively. This indicated the deletion of genetic fragments in the genome of WSSV . The WSSV isolate along with lab strain of WSSV was subjected to next‐generation sequencing. The sequence analysis revealed a deletion of 13,170 bp at five positions in the genome of WSSV ‐ NS (new strain) relative to WSSV ‐ TH and WSSV ‐ LS (lab strain). The PCR analysis using the ORF 's specific primer sets revealed the complete deletion of 10 ORF s in the genome of WSSV ‐ NS strain. The primer set was designed based on sequence covering ORF 161/162/163 to amplify a product of 2,748 bp for WSSV ‐ LS and 402 bp for WSSV ‐ NS . Our surveillance programme carried out since 2002 revealed the replacement of WSSV ‐ LS by WSSV ‐ NS in Indian shrimp culture system.

Effect of supplementing germinated sprouts of pulses on performance, carcass variables, immune and oxidative stress indicators in broiler chickens reared during tropical summer season - S. V. Rama Rao; B. Prakash; U. Rajkumar; M. V. L. N. Raju; T. Srilatha; E. P. K. Reddy (Tropical Animal Health and Production, 2018)

Neoplasia in goldlined seabream, Rhabdosargus sarba (Forsskål, 1775) - V Singaravel; A Gopalakrishnan; K Raja; M Rajkumar; H W Ferguson (Journal of Fish Diseases, 2018)

Probabilistic assessment of phenophase-wise agricultural drought risk under different sowing windows: a case study with rainfed soybean - Rajkumar Dhakar; M. A. Sarath Chandran; Shivani Nagar; V. Visha Kumari (Environmental Monitoring and Assessment, 2017)

In vitro immature embryo germination and propagation of Vanda stangeana Rchb. f., an orchid endemic to India - Bembemcha Pebam; Rajkumar Kishor; V. Narmatha Bai (Horticulture, Environment, and Biotechnology, 2016)

Development of microsatellite markers and their use in genetic diversity and population structure analysis in Casuarina - A. R. K. Kullan; A. V. Kulkarni; R. Suresh Kumar; R. Rajkumar (Tree Genetics & Genomes, 2016)

Identification and agro-morphological characterization of rice genotypes resistant to sheath blight - Susmita Dey; Jyothi Badri; V. Prakasam; V. P. Bhadana; K. B. Eswari; G. S. Laha; C. Priyanka; Aku Rajkumar; T. Ram (Australasian Plant Pathology, 2016)

Predicting Irrigated and Rainfed Rice Yield Under Projected Climate Change Scenarios in the Eastern Region of India - A. V. M. Subba Rao; Arun K. Shanker; V. U. M. Rao; V. Narsimha Rao; A. K. Singh; Pragyan Kumari; C. B. Singh; Praveen Kumar Verma; P. Vijaya Kumar; B. Bapuji Rao; Rajkumar Dhakar; M. A. Sarath Chandran; et al. (Environmental Modeling & Assessment, 2016)

Assessment of terminal heat tolerance ability of wheat genotypes based on physiological traits using multivariate analysis - Shivani Nagar; V. P. Singh; Ajay Arora; Rajkumar Dhakar; Shiv Ramakrishnan (Acta Physiologiae Plantarum, 2015)

Terbinafine hydrochloride loaded nanoemulsion based gel for topical application - V. V. S. Narayana Reddy Karri; Suresh Kumar Raman; Gowthamarajan Kuppusamy; Shashank Mulukutla; Shanmugam Ramaswamy; Rajkumar Malayandi (Journal of Pharmaceutical Investigation, 2015)

Establishing postprandial bio-equivalency and IVIVC for generic metformin sustained release small sized tablets - Chandramohan Eaga; Shivakumar Mantri; Rajkumar Malayandi; Phani Krishna Kondamudi; Sumon Chakraborty; S. V. N. Raju; Deepika Aggarwal (Journal of Pharmaceutical Investigation, 2014)

Bloom forming species of phytoplankton in two coastal waters in the Southeast coast of India - K. Thillai Rajasekar; M. Rajkumar; Jun Sun; V. Ashok Prabu; P. Perumal (Journal of Ocean University of China, 2010)

Seasonal variations of phytoplankton diversity in the Coleroon coastal waters, southeast coast of India - Rajasekar K. Thillai; M. Rajkumar; Jun Sun; Prabu V. Ashok; P. Perumal (Acta Oceanologica Sinica, 2010)

Effects of selected heavy metals (Pb, Cu, Ni, and Cd) in the aquatic medium on the restoration potential and accumulation in the stem cuttings of the terrestrial plant, Talinum triangulare Linn - K. Rajkumar; S. Sivakumar; P. Senthilkumar; D. Prabha; C. V. Subbhuraam; Y. C. Song (Ecotoxicology, 2009)

Fluorescence Quenching of 1,4-Dihydroxy-2,3-Dimethyl-9,10-Anthraquinone by Silver Nanoparticles: Size Effect - M. Umadevi; P. Vanelle; T. Terme; Beulah J. M. Rajkumar; V. Ramakrishnan (Journal of Fluorescence, 2009)

Spectral Investigations of Solvatochromism and Preferential Solvation on 1,4-Dihydroxy-2,3-Dimethyl-9,10-Anthraquinone - M. Umadevi; P. Vanelle; T. Terme; Beulah J.M. Rajkumar; V. Ramakrishnan (Journal of Fluorescence, 2008)

Iontophoretic in Vivo Transdermal Delivery of β-Blockers in Hairless Rats and Reduced Skin Irritation by Liposomal Formulation - Rajkumar Conjeevaram; Ayyappa Chaturvedula; Guru V. Betageri; Gangadhar Sunkara; Ajay K. Banga (Pharmaceutical Research, 2003)

Molecular characterization of some Indian Basmati and other elite rice genotypes using fluorescent-AFLP - R. Aggarwal; V. Shenoy; J. Ramadevi; R. Rajkumar; L. Singh (Theoretical and Applied Genetics, 2002)